KPK2S UPAYA MENINGKATKAN SIKAP DISIPLIN DAN MENGUATKAN KEMANDIRIAN PESERTA DIDIK PADA PROSES PEMBELAJARAN DI KELAS - Ahmad Ardius Kidan (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
In 2013, Indonesia has a new curriculum as a refinement of the curriculum, reflecting the demands of emotionally and socially intelligent learners to be evident in the 2013 curriculum with attitudinal attitudes on students, and the basis for the application of character education. The planting and assessment of discipline and independence attitudes done by teachers to learners has not been much, because constrained by the process and teaching techniques, teaching media and assessment instruments. Assessment of discipline attitude and independence of learners in the learning process is very important, for habituation and strengthening the character of learners. Reason for strengthening because Found learners who are not disciplined in carrying tools and materials, and not discipline in collecting tasks. Also found students who feel unappreciated, depressed due to teacher monopolized learning and not democratic, so that learners are not able to make their own decisions. To improve the discipline and strengthen the independence of learners, then used the media KPK2S. The purpose of this research activity to assess the improvement of discipline and independence of learners, the assessment is used with the observation or observation of teachers on the sheet of discipline and independence. Scoring of values based on the observation sheet, then analyzed with qualitative data analysis techniques, the results of research with the media KPK2S indicate the increase in the independent attitude and discipline of learners. Percentage of classical completeness disciplinary attitude of learners at first observation of 9.37%, on the second observation to be 100%. The increase in the percentage of classical completeness of the independent value of the learners at the first observation of 71.87% and the second observation to be 92.87%. So it shows that the percentage value of classical completeness for the attitude of discipline and the independence of learners has exceeded from the indicator of the success of classical clarity that has been set at 75%. Keywords:  KPK2S, Independence, and Discipline